Engineered Titanium Oxide Nanoplatform for Targeted Photodynamic/Photothermal-Gas Therapy in Keloid Treatment - Jin, Zilong; Dai, Wufei; Huang, Zhengjie; Li, Qinglin; Zhu, Yuduo; Wang, Wenbo; Xu, He (ACS Applied Materials and Interfaces, 2025)
Keloids pose a considerable worldwide health issue owing to their continual proliferation, invasiveness, and elevated recurrence rates. Keloids are abnormal scars formed through dysregulated wound healing processes, characterized by excessive keloid fibroblast (KF) proliferation, irregular collagen deposits, and persistent reticular dermis inflammation, which can lead to limited joint mobility, psychological distress, and severe pain and itching. In this study, we present metal-organic framework (MOF)-derived TiO2-based nanoparticles (LA@CTx NPs) synthesized as a phototherapy-gas-therapy nanoplatform, which have the ability to break down collagen, reduce inflammation, and stop the overproliferation of keloid fibroblasts. The MIL-125-derived nanoparticles maintain their crystalline framework while being rich in oxygen vacancies (OVs) and l-arginine (LA), enabling efficient photothermal conversion and reactive oxygen species (ROS) generation driven by synergistic near-infrared (NIR). Importantly, ROS generated by the NPs can trigger nitric oxide (NO) production by oxidizing LA, with the concentration of NO finely tunable via modulation of light conditions. This allows for a dual therapeutic effect: low NO concentrations suppress inflammation, while higher concentrations induce cell death. In vitro and in vivo investigations show that LA@CTx nanoparticles efficiently eliminate primary keloid lesions and provoke apoptosis in keloid cells by dual-modality activation of photodynamic and photothermal treatments facilitated by single NIR irradiation. The study presents an innovative method of therapy for the clinical treatment of keloids.
CRIS-Team Scopus Importer:2025-04-11
Keywords: gas therapy; keloids; MOF derivation; phototherapy; TiO